The Investment Supervision Implementation and One-Stop Integrated Services Office on the Implementation of Advertising in Public Spaces Based on the Regulation of the Head of Bekasi Region - Wibowo, Riyadi Saputra; Waluyo, Waluyo; Hermawan, Sapto (Strata Law Review, 2024)
This research aims to discover the supervision practices carried out by the Bekasi Regency Investment and One-Stop Service Office (PMPTSP Office) and the obstacles faced in implementing billboards in public spaces. This research is descriptive normative research. The sources of legal materials used in this research are primary and secondary legal materials, as well as library study and interview techniques. The analysis method in this research uses qualitative analysis techniques. The results of this study indicate that the supervision carried out by the Bekasi Regency PMPTSP Office on the implementation of billboards in public spaces uses a form of preventive supervision in coordination with the Pamong Praja Police Unit and the Regional Revenue Agency. The obstacles faced by the Bekasi Regency PMPTSP Office in supervising the implementation of billboards in public spaces are the lack of human resources that accommodate the authority, the level of public legal awareness regarding the implementation of billboards, and the development of regulations that are not integrated and develop along with economic growth in the free market era.